Effects of caffeine or RX821002 in rats with a neonatal ventral hippocampal lesion - Sandner, Guy; Angst, Marie-Josée; Guiberteau, Thierry; Guignard, Blandine; Nehlig, Astrid (Frontiers in Behavioral Neuroscience, 2014)
Rats with a neonatal ventral hippocampal lesion (NVHL) are used to model schizophrenia. They show enhanced locomotion and difficulties in learning after puberty. Such behavioural modifications are strengthened by dopaminergic psychostimulant drugs, which is also relevant for schizophrenia because illustrating its dopaminergic facet. But it remains questionable that only dopaminergic drugs elicit such effects. The behavioural effects could simply represent a non specific arousal, in which case NVHL rats should also be hyper-responsive to other vigilance enhancing drugs. We administered an adenosine (caffeine) or an adrenaline receptor antagonist, (RX821002) at doses documented to modify alertness of rats, respectively 5 mg/Kg and 1 mg/Kg. Rats were selected prior to the experiments using MRI (magnetic resonance imaging). Each group contained typical and similar NVHL lesions. They were compared to sham lesioned rats. We evaluated locomotion in a new environment and the capacity to remember a visual or acoustic cue that announced the occurrence of food. Both Caffeine and RX82100 enhanced locomotion in the novel environment, particularly in NVHL rats. But, RX82100 had a biphasic effect on locomotion, consisting of an initial reduction preceding the enhancement. It was independent of the lesion. Caffeine did not modify the learning performance of NVHL rats. But, RX821002 was found to facilitate learning. Patients tend to intake much more caffeine than healthy people, which has been interpreted as a means to counter some cognitive deficits. This idea was not validated with the present results. But adrenergic drugs could be helpful for attenuating some of their cognitive deficits.